Business, Politics and Public Policy
XVIII, 327 p. 2 illus.
Keywords: This is the second volume on the changing nature of state-business relations. This book examines how the dynamics of business have influenced public policy in the context of economic liberalization and democratization. It identifies the circumstances under which business might support progressive policies in developing countries.